Variability of the modified Balance Error Scoring System at baseline using objective and subjective balance measures - Amaal J Starling; Danielle F Leong; Jamie M Bogle; Bert B Vargas (Concussion)
Aim: To investigate preseason modified Balance Error Scoring System (mBESS) performance in a collegiate football cohort; to compare scores to an objective mobile balance measurement tool. Materials & methods: Eighty-two athletes completed simultaneous balance testing using mBESS and the King–Devick Balance Test, an objective balance measurement tool. Errors on mBESS and objective measurements in the double-leg, single-leg (SS) and tandem stances were compared. Results: Mean mBESS error score was 7.23 ± 4.65. The SS accounted for 74% of errors and 21% of athletes demonstrated the maximum error score. There was no significant correlation between mBESS score and objective balance score. Conclusion: The high variability and large number of errors in the SS raises concerns over the utility of the SS in identifying suspected concussion.